2022
DOI: 10.1021/acs.jafc.2c02015
|View full text |Cite
|
Sign up to set email alerts
|

Orientin Attenuatedd-GalN/LPS-Induced Liver Injury through the Inhibition of Oxidative Stress via Nrf2/Keap1 Pathway

Abstract: Oxidative stress is involved in the pathogenesis of liver diseases, including liver injury, a serious health problem worldwide. Natural polyphenols have attracted increasing attention as potential agents for the prevention and treatment of liver diseases. Orientin, a flavonoid component with antioxidant capacity, has been regarded as a promising nutraceutical for patients with liver damage. This study aimed to investigate the amelioration effect of orientin on D-galactosamine and lipopolysaccharides (D-GalN/LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Surprisingly, luteolin-6-C-glucoside is a luteolin derivative [ 26 ] that has many health-promoting benefits such as antioxidation and anti-inflammation [ 27 ]. Orientin, a flavonoid component with antioxidant properties, has been regarded as a promising nutraceutical for patients with liver damage [ 28 ]. Presently, they are mainly extracted from plants in a process characterized by high cost, low content, and long growth cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, luteolin-6-C-glucoside is a luteolin derivative [ 26 ] that has many health-promoting benefits such as antioxidation and anti-inflammation [ 27 ]. Orientin, a flavonoid component with antioxidant properties, has been regarded as a promising nutraceutical for patients with liver damage [ 28 ]. Presently, they are mainly extracted from plants in a process characterized by high cost, low content, and long growth cycle.…”
Section: Discussionmentioning
confidence: 99%
“…As important antioxidant enzymes, SOD catalyzes the formation of hydrogen peroxide (H 2 O 2 ) from superoxide radicals, and CAT further degrades H 2 O 2 into water. GSH-Px also plays a role in eliminating peroxides and hydroxyl radicals [ 25 ]. Additionally, non-enzymatic antioxidants, such as GSH, vitamins, and ubiquinone, directly scavenge ROS, which can be indirectly reflected by the T-AOC [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that orientin had a role in the amelioration of liver damage by lowering oxidative stress. This suppression of oxidative stress may be closely connected to the activation of Nrf2/ARE, which occurs through the phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) and P38/MAPK signal pathways [ 45 ]. Additionally, using the Nrf2 and NF-κB signaling pathways, a polysaccharide called PFP-1 from the Pleurotus geesteranus fungus can reduce the severity of alcoholic liver disorders [ 46 ].…”
Section: Liver Impairment Mediated By Mitochondrial Reactive Oxygen S...mentioning
confidence: 99%